Rapid screening of pea (Pisum sativum) genotypes against aluminium toxicity - ANSARI, MOHD TALHA; SARMA, P; KUMAR, SANDEEP; SHANKAR, KRIPA (The Indian Journal of Agricultural Sciences, 2023)
Twenty-five pea genotypes were grown in trays under a controlled environment in the laboratory of Basic Sciences and Humanities, College of Horticulture and Forestry, CAU, Pasighat, Arunachal Pradesh (2018–2021) and evaluated at 3 levels of Al (0 ppm, 12 ppm and 24 ppm). Al treatment was given through Hoagland solution. Screening of pea genotypes was performed using growth characters, root tolerance index and haematoxylin staining. The genotypes Kashi Samridhi, CHFGP-1 and CHFGP‑14 exhibited an increase in root and shoot biomass. Nearly all the genotypes exhibited reduction in root and shoot length. Based on the K-clustering score P.S.M.3, Kashi Samrath, Kashi Samridhi, CHFGP-1, CHFGP-7 and CHFGP-55 were observed as tolerant at 24 ppm Al level. Matar Ageta-7, Pb-89, AP-3, Pusa Pragati, Arka Priya, Kashi Shakti, CHFGP-6, VRPE- 29, NO-17 and CHFGP-15 were categorized as susceptible genotypes.a